2001
DOI: 10.1016/s0969-2126(01)00617-7
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of the MJ1267 ATP Binding Cassette Reveal an Induced-Fit Effect at the ATPase Active Site of an ABC Transporter

Abstract: The induced-fit effect and rotation of the alpha-helical subdomain may play a role in controlling the nucleotide-dependent change in cassette-cassette interaction affinity believed to represent the power-stroke of ABC transporters. Outward rotation of the alpha-helical subdomain also likely facilitates Mg-ADP release after hydrolysis. The MJ1267 structures therefore define features of the nucleotide-dependent conformational changes that drive transmembrane transport in ABC transporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
312
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 284 publications
(346 citation statements)
references
References 60 publications
30
312
1
1
Order By: Relevance
“…However, an extensive structural analysis was performed to address dimer formation. Special attention was placed on the solvent-accessible surface area (ASA), buried in the dimer interface of HisP, MalK, Rad50cd and the potential dimers of MJ0796 and of MJ1267 (Karpowich et al 2001a). The analysis revealed that, with the exception of Rad50cd and MalK, all the ASAs were equivalent to those commonly found for crystal packing contacts, rather than for oligomeric complexes (Janin 1997).…”
Section: Dimeric Arrangement -Problems and Solutionsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, an extensive structural analysis was performed to address dimer formation. Special attention was placed on the solvent-accessible surface area (ASA), buried in the dimer interface of HisP, MalK, Rad50cd and the potential dimers of MJ0796 and of MJ1267 (Karpowich et al 2001a). The analysis revealed that, with the exception of Rad50cd and MalK, all the ASAs were equivalent to those commonly found for crystal packing contacts, rather than for oligomeric complexes (Janin 1997).…”
Section: Dimeric Arrangement -Problems and Solutionsmentioning
confidence: 99%
“…This suggests that, upon ATP binding, these regions might be stabilized and possibly also take on another position in the ATP bound state. Furthermore, Karpowich et al (2001b) extensively analyzed the B-factors in the different nucleotide bound forms of MJ1267. Here the nucleotide-free structure shows higher overall B-factors compared to the Mg*ADP bound form.…”
Section: The Intrinsic Flexibility Of the Apo Nbd Formsmentioning
confidence: 99%
See 3 more Smart Citations